1300°C Annealing of 1 × 1020 cm−3 Al+ Ion Implanted 3C-SiC/Si. (21st August 2019) - Nipoti, Roberta; Canino, Mariaconcetta; Zielinski, Marcin; Torregrosa, Frank; Carnera, Alberto
Abstract : The 4H-SiC polytype has been here used as a benchmark to see that, in the case of ion implanted 1 × 10 20  cm −3 Al, a carrier transport in the implanted layer is measurable after 1350°C post implantation annealing, provided that the annealing time is sufficiently long. This opens the way to the possibility of studying the post implantation annealing of ion-implanted 3C-SiC/Si at temperatures that avoid the risk of melting the Si substrate. The post implantation annealing of 1 × 10 20  cm −3 Al + ion implanted 3C-SiC/Si at 1300°C for annealing times in the range 90–546 h has been here performed. The results of Secondary Ion Mass spectrometry, Atomic Force Microscopy, Fourier Transform Infra-Red reflectance spectroscopy, X-Ray Diffraction spectroscopy, and current-voltage measurements by the transmission line method are presented and discussed.